Scienceploration 2023 - Tan Geok Shim, George; Dhana Jay, Raja Gopal; Melisa Malini, Raja Gopal; Mohamad Razif, Othman; Dzetty Soraya, Abdul Aziz; Ibrahim, Bohari; Abdul Al-Hafiz, Ismail; Michelle, George; Maybelline Goh, Boon Ling; Mohd Aminudin, Mustapha; Norfarahin, Norwen; Mohamad Fhaizal, Mohamad Bukhori; et al. (Centre for Pre-University Studies, 2023)
The Scienceploration Camp is an initiative of the Centre for Pre-University Studies, UNIMAS (PPPU), which aims to increase the interest in science among secondary school students. It is also an effort taken by PPPU towards the achievement of Sustainable Development Goals 4 in providing equal quality education and promoting lifelong learning opportunities for all. On top of that, this camp supports Sarawak’s Digital Economy Strategy in nurturing an integrated ecosystem to foster inclusive digital society, by building the right foundations to grow our local digital economy.